DETERMINANT FACTOR OF CONDOM USE AMONG MEN SEX MEN AND TRASNGENDER WOMEN IN SOUTHEAST ASIA REGION : A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v1i2.22 - Khumaidi Khumaidi; Yona Sri (Alta Dharma Publisher, 2018)
Abstract Background : based on data from UNAIDS 2017 reported that men sex men(MSM) and other MSM (transgender women) accounted for 12 percent of new HIV infections in 2017. The Asia Pacific region is one of the regions that contributes new HIV cases from MSM and transgender women. Unprotected anal sex is a major cause of HIV transmission among MSM and transgender women. Objective: the study aimed to describe determinan factors of condom use among men sex men and transgender women in Southeast Asia region. Methods : we search literature from various relevant sources. Five databases including PubMed, PROQUEST, Plos One, Science Direct and Ebsco were included in this study. Results : several factors that contribute to condom use such as individual factors including attitudes, knowledge related to HIV, decreased sexual pleasure, substance use and gender presentation. Other factors that influence condom use are family support, peer support and experience of physical violence and sexual abuse. the type of partner and the amount of pay for sex among transgender women also influence condom use. Conclusion :several factors are noted from individual, social, family and sex partner. Further research especially intervention research, it is necessary to consider the factors that influence condom use before developing interventions for MSM and transgender women.